Residents’ Perception of Radon Health Risk: A Qualitative Study - Khan SM, Chreim S (Université d'Ottawa | University of Ottawa, 2019)
Background: Radon is a high impact environmental pollutant and is the second leading cause of lung cancer in Canada. Building design, extended winter, and geographical location expose residents of Ottawa-Gatineau (the national capital region in Canada) to an increased risk. It is surprising that residents have an inadequate awareness of the risk - despite its gravity - and have taken minimum preventive actions. This study explores perceptions of radon health risk and examines the factors that enable and hinder the adoption of preventive measures among Ottawa-Gatineau residents. Methods: We conducted semi-structured interviews with 35 residents from varying educational levels and occupational backgrounds to inquire about their knowledge and perception of radon, and to explore their views of enablers and obstacles to taking action to reduce radon risks. Thematic, inductive data analysis was undertaken. Results: The results indicate that: 1) Residents obtained information on radon from various sources - the media, self-education or occupation, social network, and home renovation events. Limited references were made to the National Radon Program responsible for testing for radon and informing residents. 2) Awareness of radon risk varies, knowledge retained by some residents is insufficient to protect their health adequately. Residents who had dual perceptions- cognitive as well as emotional awareness, motivated enough to act. 3) Enablers for taking protective action: understanding the risk along with health consciousness; caring for family and children; knowing others who had contracted lung cancer and having financial resources. Obstacles included: lack of awareness; cost; lack of home ownership; and potential difficulty in selling the house. 4) Residents attributed primary responsibility to public agencies for disseminating information and incentivizing or mandating action through more stringent regulation. Conclusion: Risk perceptions are subjective and influenced by the micro and macro level factors. Inducing protective action requires complex interventions considering dual perceptions of the threat by the public health agencies.
Keywords: Radon; Risk perception; Testing; Mitigation; Enabler; Barrier; Health Communication